Haptoglobin is required to prevent oxidative stress and muscle atrophy. - Enrico Bertaggia; Gaia Scabia; Stefania Dalise; Francesca Lo Verso; Ferruccio Santini; Paolo Vitti; Carmelo Chisari; Marco Sandri; Margherita Maffei (PLoS ONE)
Background Oxidative stress (OS) plays a major role on tissue function. Several catabolic or stress conditions exacerbate OS, inducing organ deterioration. Haptoglobin (Hp) is a circulating acute phase protein, produced by liver and adipose tissue, and has an important anti-oxidant function. Hp is induced in pro-oxidative conditions such as systemic inflammation or obesity. The role of systemic factors that modulate oxidative stress inside muscle cells is still poorly investigated. Results We used Hp knockout mice (Hp-/-) to determine the role of this protein and therefore, of systemic OS in maintenance of muscle mass and function. Absence of Hp caused muscle atrophy and weakness due to activation of an atrophy program. When animals were stressed by acute exercise or by high fat diet (HFD), OS, muscle atrophy and force drop were exacerbated in Hp-/-. Depending from the stress condition, autophagy-lysosome and ubiquitin-proteasome systems were differently induced. Conclusions Hp is required to prevent OS and the activation of pathways leading to muscle atrophy and weakness in normal condition and upon metabolic challenges.